The effect of audit committee effectiveness on audit report delay: an examination on Shariah compliant companies / Siti Fabillah Mohd Yunos - Mohd Yunos, Siti Fabillah (2012)
This study examines the relationship between audit committee effectiveness and the audit report delay among the Shariah-Compliant companies which focus on audit committee independence, audit committee meeting and audit committee expertise. Furthermore, this study also looks at the relationship between the size of the company and the financial year end on the audit report delay. The data are collected using content analysis from annual report for 507 companies from year 2006 until 2008. The audit report delay form 2006 to 2008 is between 40 to 141 days. This study uses multiple regression analysis. The findings show that audit report delay will be longer for companies with higher number of audit committee meetings and will be shorter for larger companies besides having more financial expert in audit committee members. The result also finds that the composition of non-executives directors in audit committee and financial year-end does not give any significant influence to the audit report delay.